Adab Bergaul dan Bertoleransi dalam Interaksi Sosial Peserta Didik Beda Agama - Febrianti, Ade; Hasmy, Ali; Usman, Usman (Advances In Social Humanities Research, 2024)
As a country with a multicultural population composition, the Indonesian population is very familiar with the issues of the halal and unlawful status of food, social etiquette and the practice of tolerance. So, it is very urgent to immediately formulate the theme of Islamic study material as part of multicultural insight lessons such as in the Kembayan District area, Sanggau, West Kalimantan. The aim of this research is to formulate Islamic ideals regarding the etiquette of getting along and being tolerant in the social interactions of Muslim and non-Muslim students so that education can actually become a forum that guides and directs students, especially those who are Muslim, so that they do not fall into negative relationships because they are wrong define the meaning of tolerance. This paper uses a descriptive qualitative research method with a type of library research which examines in depth the library materials that are relevant to the theme of the material being discussed. The main sources for this article are taken from books, journal articles, internet articles and other related writings. The technique used in collecting data in this paper uses secondary data, namely by collecting data indirectly by examining the object in question.